EFFECTS OF KAINIC ACID ON GLUTATIONE AND NITRITE IN RAT HIPPOCAMPUS - Nadka I. Boyadjieva; Pavlina Andreeva-Gateva (Peytchinski Publishing, 2011)
Epileptiformic activity could result in apoptotic neuronal death, in which oxidative stress could play an important role. In case of decreased antioxidant brain status cellular death could be facilitated. Kainic acid is often used in a model of epilepsy in rats. Up to now there is not enough data evaluating levels of glutathione and nitric oxide in kainic acid-induced epilepsy acutely and several days after the kainic acid exposure. This information will be useful for assessing long term prognosis on a risk of further brain damage.We studied hippocampal levels of glutathione and nitric oxide at the 3th hour (acute group) and after 7 days of kainic (chronic group) acid exposure. We found that glutathione level is statistically significantly lower in the hippocampus 7 days after kainic acid exposure, as compared with values measured in the acute group. For both kainic acid treated groups glutathione levels were significantly lower than controls.Levels of nitric oxide were found to be significantly higher 7 days after kainic acid exposure as compared with acute group. For both kainic acid treated groups nitric oxyde levels were significantly lower than controls.We conclude that in kainic acid treated rats oxidative stress could be present even after a single treatment. This could be a potentially pathogenic factor for further brain damages.